My baby is coming - Mohd Arifin, Siti Roshaidai (2017)
Labour is a process by which the products of conception are expelled from the uterus. This talk was delivered to the pregnant mothers. It covers the following topics: understanding women’s reproductive system, baby’s growth and development, labour and delivery process, childbirth laceration and its management.